The Development and Research of Auxiliary Power Supply System of the Metro Vehicles - 赵清良; 刘清; 曾明高 (机车电传动)
General requirements of the auxiliary power supply system for urban rail trains were introduced. Scheme of the power system and circuits were described to analyze the system integration principle. Technic development and applications of the homemade auxiliary power system were presented.